What the health care administrator needs to consider when purchasing personal computers. - Campbell RJ (Health Care Manager)
With personal computer (PC) sales expected to grow by 10.3% in the upcoming year, health care administrators, concerned with keeping their facilities equipped with the latest technology while maintaining the bottom line, will need to be aware of the components that are designed for today's personal computer. This knowledge will enable them to match the functionality needed by end-users with the technology afforded by available PCs, thereby ensuring that costly computers that exceed the users' needs and expectations are not purchased. This article provides health care administrators the requisite specifications and guidelines to make informed choices.